2020
DOI: 10.1007/s00520-020-05371-7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, perceptions and practices regarding cancer-related malnutrition and sarcopenia: a survey of cancer clinicians

Abstract: Cancer-related malnutrition and sarcopenia have severe negative consequences including reduced survival and reduced ability to complete treatment. This study aimed to determine the awareness, perceptions and practices of Australian oncology clinicians regarding malnutrition and sarcopenia in people with cancer. MethodsA national cross-sectional survey of Australian cancer clinicians was undertaken between November 2018 and January 2019. The 30-item online purpose-designed survey was circulated through professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 28 publications
4
41
1
1
Order By: Relevance
“…Although several observational studies suggest the benefit of nutritional support in patients receiving chemo- or radiation therapy [ 12 ], the literature shows that it has not been adequately considered by oncologists, yet [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In these articles, the authors identify several factors acting as barriers to early use of nutritional treatment in cancer patients.…”
Section: Prevalencementioning
confidence: 99%
“…Although several observational studies suggest the benefit of nutritional support in patients receiving chemo- or radiation therapy [ 12 ], the literature shows that it has not been adequately considered by oncologists, yet [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In these articles, the authors identify several factors acting as barriers to early use of nutritional treatment in cancer patients.…”
Section: Prevalencementioning
confidence: 99%
“…Many HCPs have realized the importance of nutritional management in patients with cancer. [ 8 22 25 26 ] However, few nurses and HCPs understood the etiology and management of cancer cachexia, possibly due to a lack of pre-and post-registration education. [ 8 23 24 ] Some reports indicated that HCPs did not realize the unfavorable impact of cancer cachexia on patients' activities of daily living or sarcopenic status.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 23 24 ] Some reports indicated that HCPs did not realize the unfavorable impact of cancer cachexia on patients' activities of daily living or sarcopenic status. [ 8 26 ] In addition, one survey in the US reported that few doctors knew that cancer cachexia was often present even in patients with good performance status who were indicated for active cancer treatment. [ 25 ] Cachectic patients and their caregivers reported worrying about appetite loss, change in appearance, and reduced social activity, and also expressed that they received little information concerning cancer cachexia from HCPs.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to improving care largely include inadequate time and services and varying perception of responsibility for identification and treatment. 26 Nevertheless, international studies demonstrate failure to improve care has a considerable financial burden that is likely to translate to a similar impact on the Australian health care system. 27,28 This document outlines the position of Clinical Oncology Society of Australia (COSA) on the role of health professionals and health services in recognising and treating patients with cancer-related malnutrition and sarcopenia, with a focus on practice tips to support implementation of optimal management.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, considerable variation in screening, diagnosis and intervention occurs across Australian health care settings. Barriers to improving care largely include inadequate time and services and varying perception of responsibility for identification and treatment 26 . Nevertheless, international studies demonstrate failure to improve care has a considerable financial burden that is likely to translate to a similar impact on the Australian health care system 27,28…”
Section: Introductionmentioning
confidence: 99%